THE PRINCIPAL’S LEADERSHIP STYLE IN EMPOWERING EDUCATORS IN SCHOOLS - Wibowo, Hendro Nur; Saleh, Muhammad; Effendi, Rustam (Journal of K6, Education and Management, 2020)
The purpose of this study is to describe the leadership style of the Principal of Banjarmasin 5 Vocational High School in empowering educators. This is descriptive research. The data collection techniques were triangulation and included interviews, observation, and documentation. The results of this research showed applied leadership style is participative, as evidenced by the involvement of all school members in key aspects such as the school program, joint decision, personal selection and delegation of authority, information disclosure, and communication. The results of this research might be used as a basis for applying leadership styles in other schools.